Analisis Model Pendistribusian Zakat Produktif Baznas Kabupaten Tanah Datar (Kajian Empiris di Nagari Parambahan Kecamatan Lima Kaum) - Widi Nopiardo Nopiardo (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2020)
Â The problem in this research is the unknown detail about the distribution of productive of zakat in Nagari Parambahan and this study aims to determine the effectiveness of the distribution of productive zakat models. The type of research is a field research which is described in a descriptive qualitative manner. Data collected by using interviews and documentation and analyzed with data reduction, data presentation, and drawing conclusions related to the distribution of zakat. The results showed that productive zakat assistance conducted by BAZNAS has not been effective in the framework of developing mustahik business. There are still many undeveloped mustahik businesses, as follows: for livestock businesses out of 23 mustahik who receive assistance in the form of animals livestock (goats / ducks) there are 11 mustahik that are developing and 12 are not developing, while for agriculture out of 5 mustahik who receive productive zakat assistance, none of them are developing, while for business capital of 11 mustahik there are 4 mustahik whose business is developing and 7 not developing, and for assistance in the form of a home industry of 4 years, only 1 person mustahik who get home industry assistance, namely in 2018 and developing.Â